Structural Basis of Dynamic Membrane Recognition by trans-Golgi Network Specific FAPP Proteins. Issue 4 (27th February 2015) - Lenoir, Marc; Grzybek, Michał; Majkowski, Michał; Rajesh, Sandya; Kaur, Jaswant; Whittaker, Sara B.-M.; Coskun, Ünal; Overduin, Michael
Abstract: Glycosphingolipid metabolism relies on selective recruitment of the pleckstrin homology (PH) domains of FAPP proteins to the trans-Golgi network. The mechanism involved is unclear but requires recognition of phosphatidylinositol-4-phosphate (PI4P) within the Golgi membrane. We investigated the molecular basis of FAPP1-PH domain interactions with PI4P bilayers in liposome sedimentation and membrane partitioning assays. Our data reveals a mechanism in which FAPP-PH proteins preferentially target PI4P-containing liquid disordered membranes, while liquid ordered membranes were disfavored. Additionally, NMR spectroscopy was used to identify the binding determinants responsible for recognizing trans-Golgi network-like bicelles including phosphoinositide and neighboring lipid molecules. Membrane penetration by the FAPP1-PH domain was mediated by an exposed, conserved hydrophobic wedge next to the PI4P recognition site and ringed by a network of complementary polar residues and basic charges. Our data illuminates how insertion of a structured loop provides selectivity for sensing membrane fluidity and targeting to defined membrane zones and organelles. The determinants of this membrane sensing process are conserved across the CERT, OSBP and FAPP family. Hence, lipid gradients not only result in differential membrane ordering along the secretory pathway but also specifically localize diverse proteins through recognition of ensembles of lipid ligands in dynamic and deformable bilayers in order to promote anterograde trafficking. Graphical abstract: Highlights: FAPP-PH domains selectively recognize PI4P within disordered membrane domains. Two-pronged multistep binding mode mediates protein insertion into fluid bilayer. Protein targeting to Golgi driven by disorder gradient created by lipid composition.